N-ALKANE DEGRADATION BY MARINOBACTER HYDROCARBONOCLASTICUS STRAIN SP 17: LONG CHAIN β-HYDROXY ACIDS AS INDICATORS OF BACTERIAL ACTIVITY - Lattuati A.; Metzger P.; Acquaviva M.; Bertrand J.C.; Largeau C. (My University, 2002)
The lipids of the Gram-negative marine bacterium Marinobacter hydrocarbonoclasticus, cultivated in synthetic seawater on a single carbon source, acetate or n-icosane, were isolated, purified and their structures determined. Three different pools of lipids were isolated according to the sequential procedure used: ''unbound'' lipids extractable by solvents, lipids released under basic conditions (''ester bound'') and lipids released by acid hydrolysis (''amide bound''). Even-carbon-numbered, n-fatty acids were identified in the ''unbound'' lipids of both the acetate and n-icosane cultures. In addition to these compounds, n-icosane induced the formation of n-icosan-1-ol and n-icos-11-en-1-ol, and also of a series of β-hydroxy acids ranging from C12 to C20. In the ''ester bound'' lipids of the two cultures, short and long chain fatty acids were identified together with the β-hydroxy C12:0 acid. This hydroxy acid was, by far, the major compound identified in the ''amide bound'' lipids of the two cultures. Comparison of the analytical data for the two cultures, and the differences in composition thus observed for the ''unbound'' pool, suggest the following metabolic pathway for n-icosane: hydroxylation to the C20 primary alcohol, transformation into the C20 β-hydroxy acid and subsequent degradation into lower homologues. In sharp contrast, lipids from the ''ester bound'' and ''amide bound'' pools were quite unaffected by the change of nutrient. Lipids from Escherichia coli were also examined in the same manner. The results are discussed in terms of geochemical implications, relative to the presence of ''unbound'' β-hydroxy acids in particulate matter and sediments.
Keywords: N-ALKANES; BIODEGRADATION; FATTY ALCOHOLS; FATTY ACIDS; HYDROXY FATTY ACIDS; MARINOBACTER HYDROCARBONOCLASTICUS; ESCHERICHIA COLI